1983
DOI: 10.1177/089686088300300206
|View full text |Cite
|
Sign up to set email alerts
|

Effective Use of Amino Acid Dialysate over four Weeks in CAPD Patients

Abstract: We studied the effectiveness, tolerance to, and beneficial metabolic effects of amino acid dialysate over an intermediate period in six CAPD patients. Two liters of 1% amino acid solution (Amino-Dianeal) were alternated with dialysate containing glucose. After four weeks there were significant increases in BUN (from 64 to 102 mg%), total body nitrogen (from 1333 to 1380 g), serum transferrin (from 175 to 222 mg%) and anion gap (from 15.1 to 17.3). Initially, there was a significant rise in HDL cholesterol, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
3

Year Published

1984
1984
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(23 citation statements)
references
References 10 publications
1
19
3
Order By: Relevance
“…The present results agree with those of two previous reports (7,8). Williams et al (7) have reported that peritoneal dialysis with a 2% amino acid solution resulted in an average ultrafiltration volume of 571 ml during 6 h dwell, compared with 566 ml for Dianeal glucose 4.25%.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present results agree with those of two previous reports (7,8). Williams et al (7) have reported that peritoneal dialysis with a 2% amino acid solution resulted in an average ultrafiltration volume of 571 ml during 6 h dwell, compared with 566 ml for Dianeal glucose 4.25%.…”
Section: Discussionsupporting
confidence: 93%
“…Oren et a]. (8) have reported that the use of a 1% amino acid solution (two liters per day alternated with dialysis fluid containing glucose) over 4 weeks in 6 CAPD patients resulted in an average increase in BUN levels by 60% whereas the changes in fasting plasma amino acid levels were small. On the other hand, the present results show that the hyperglycemic stress during CAPD with glucose solutions can be decreased by using amino acid solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Oreopoulos and colleagues studied the effects of amino acid-containing solutions in an attempt to reduce amino acid losses from the peritoneal effl uents and prevent hypertriglyceridemia and obesity. 47,48 These early studies suggested that amino acids could be potential osmotic agents without interfering with nitrogenous waste removal. Increased levels of albumin, pre-albumin, and transferrin have been observed after 1-3 months of treatment with amino acid dialysate in hypoalbuminemic PD patients.…”
Section: New Osmotic Agentsmentioning
confidence: 99%
“…51 In addition, signifi cant and progressive increase in blood urea nitrogen (BUN) concentrations and the possible development of clinical metabolic acidosis have been observed with the use of amino acidcontaining PD solutions. 47,[53][54][55][56] Glucose-based biocompatible solutions. New glucose-based biocompatible solutions are available in double-or triple-chamber bags, where the glucose is separated from the buffer and electrolyte components.…”
Section: New Osmotic Agentsmentioning
confidence: 99%